Ear, nose and throat and head and neck surgery an illustrated colour text - Dhillon, R.S; East, C. A. (Illustrated colour text)
A textbook in the Illustrated Colour Text series on ENT, aimed at medical students and junior doctors. Concise presentation of ENT in the attractive ICT format - clear line diagrams, colour photos of clinical conditions, summary boxes etc. Covers a topic which is important in primary care - medical students and junior doctors are motivated to buy a book in this area. Basic anatomy and physiology is reviewed - useful revision for students in clinical years.Comprehensive coverage of both presenting symptoms and specific diseases, with more detail on the commoner conditions. Clear description of exam